Compartmental distribution of striatal cell bodies expressing [Met]enkephalin-like immunoreactivity. - Graybiel, A M (1984)
Striatal cell bodies and fibers expressing [Met]enkephalin [( Met]Enk)-like immunoreactivity were studied with two variants of the peroxidase-antiperoxidase method in normal primates and cats and in cats pretreated with colchicine. Strikingly different patterns of [Met]Enk-like immunoreactivity were observed, both in fiber and cell body immunostaining, depending on the technical protocols followed; no single histochemical protocol fully revealed the compartmentalization present. In the dorsal striatum, patches of [Met]Enk-positive neuropil, known to line up with the acetylcholinesterase-poor striatal zones called striosomes, appeared in sections treated by protocols favoring fiber immunostaining. In sections stained by procedures favoring perikaryal staining, the striosomes appeared as Enk-poor patches in a field of immunoreactive cells and neuropil. When cell-body staining was enhanced by pretreatment with colchicine, cells expressing [Met]Enk-like immunoreactivity appeared both in and out of striosomes, and the striosomal neuropil appeared Enk-rich. These results suggest that there are subtypes of Enk-positive neurons in the striatum, including a "colchicine-dependent subtype" in dorsal striosomes, and suggest that the Enk-positive striatal neuropil is also made up of different components. Immunospecificity of this dorsal striosomal system was further demonstrated by the finding that neurons expressing intense immunoreactivity to substance P and to dynorphin B were largely confined to striosomes.